“Tukar Gawan” Tradisi Jawa Kirim Doa Jumat Legi di Desa Ngebruk - Aulia Novianty Ardini; Ali Badar (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
The tradition of exchanging gawan is one of the original cultures of the Ngebruk village community, which is still carried out today as a form of respect for ancestors. "Tukar Gawan," which means "exchanging luggage," refers to the practice of bringing food to a Friday Legi prayer event, where participants exchange their own food for that of others. The purpose of writing this article is to understand the meaning of the gawan exchange tradition in maintaining peace between residents in Ngebruk Village and the dynamics that occur in the gawan exchange tradition. The method used in this research is a descriptive qualitative method. In collecting data, the author used observation, interview, and documentation techniques. Peace is a basic thing for human life that will bring calm and harmony to interactions between people. Apart from that, peace also provides an opportunity for humans to build a better civilization than before. We obtained research data through in-depth interviews with Mr. Miskam, the village elder of Ngebruk, and then used Emile Durkheim's theory of social solidarity for descriptive analysis. The results of this research are: (1) Stages or process of implementing the gawan exchange tradition; (2) The tradition of exchanging friends invites residents to help each other; (3) The tradition of exchanging bridesmaids invites people to consciously create harmony and sincerity; (4) The tradition of exchanging gawan invites residents to be sensitive to the conditions of society through giving alms; (5) Prohibition of discriminating against existing differences; (6) Appeal to strengthen ties of brotherhood between residents; and (7) Awareness of human equality; (8) The dynamics that occur in the Javanese tradition of sending Friday Legi prayers in Ngebruk Village, Poncokusumo District, Malang Regency.